Impaired bone formation and increased osteoclastogenesis in mice lacking chemokine (C‐C motif) ligand 5 (Ccl5). (18th September 2013) - Wintges, Kristofer; Beil, F Timo; Albers, Joachim; Jeschke, Anke; Schweizer, Michaela; Claass, Benjamin; Tiegs, Gisa; Amling, Michael; Schinke, Thorsten
ABSTRACT: Chemokines play crucial roles in the recruitment of specific hematopoietic cell types, and some of them have been suggested to be involved in the regulation of bone remodeling. Because we have previously observed that chemokine (C‐C motif) ligand 2 ( Ccl2 ) and Ccl5 are direct target genes of noncanonical Wnt signaling in osteoblasts, we analyzed the skeletal phenotypes of Ccl2 ‐deficient and Ccl5 ‐deficient mice. In line with previous studies, Ccl2 ‐deficient mice display a moderate reduction of osteoclastogenesis at the age of 6 months. In contrast, 6‐month‐old Ccl5 ‐deficient mice display osteopenia associated with decreased bone formation and increased osteoclastogenesis. Moreover, unlike in wild‐type and Ccl2 ‐deficient mice, large areas of their trabecular and endocortical bone surfaces are not covered by osteoblasts or bone‐lining cells, and this is associated with a severe reduction of endosteal bone formation. Although this phenotype diminishes with age, it is important that we could further identify a reduced number of osteal macrophages in 6‐month‐old Ccl5 ‐deficient mice, because this cell type has previously been reported to promote endosteal bone formation. Because Ccl5 ‐deficient mice also display increased osteoclastogenesis, we finally addressed the question of whether osteal macrophages could differentiate into osteoclasts and/or secrete inhibitors of osteoclastogenesis. For that purpose we isolated these cells by CD11b affinity purification from calvarial cultures and characterized them ex vivo. Here we found that they are unable to differentiate into osteoblasts or osteoclasts, but that their conditioned medium mediates an antiosteoclastogenic effect, possibly caused by interleukin‐18 (IL‐18), an inhibitor of osteoclastogenesis expressed by osteal macrophages. Taken together, our data provide in vivo evidence supporting the previously suggested role of Ccl5 in bone remodeling. Moreover, to the best of our knowledge, Ccl5 ‐deficient mice represent the first model with a spontaneous partial deficiency of osteal macrophages, a recently identified cell type, whose impact on bone remodeling is just beginning to be understood. © 2013 American Society for Bone and Mineral Research.